Investigation of Anisotropic Cylindrical Semiconductor-Dielectric Waveguides - Plonis, Darius; Malisauskas, Vacius; Katkevicius, Andrius (Elektronika ir Elektrotechnika, 2015)
The use of semiconductor-dielectric waveguides is low at the moment due to disadvantage of high attenuation of electromagnetic microwaves. The attenuation depends on structures and materials of semiconductor-dielectric waveguides. Dependences of transmission coefficient on the frequency of semiconductor-dielectric waveguides and on different densities of electrons in semiconductors are studied in this paper. As well as the influence of periodicity on transmission of electromagnetic microwaves in semiconductor-dielectric waveguides is discussed. It is shown that frequency dependences of transmission coefficient of periodical semiconductor-dielectric waveguides obtain the properties of the band pass filter. Also it is shown that the choice of semiconductor and dielectric materials have a significant impact on the nature of the transmission and attenuation of electromagnetic microwaves.DOI: http://dx.doi.org/10.5755/j01.eee.21.5.13327